(untitled) (Swiss Medical Weekly, 2010)
With reference to the Year of the Lung, current knowledge of the respiratory effects of current ambient air pollution is reviewed. Acute respiratory effects are well established. Studies such as SAPALDIA and others now shed light on the long-term effects on chronic pathologies and on the health benefit of air quality improvements. The identification of those at highest risk and of local effects of not yet regulated traffic-related pollutants remains a research priority.